1988
DOI: 10.1093/aesa/81.2.209
|View full text |Cite
|
Sign up to set email alerts
|

A New Species of Manure-Inhabiting Mite in the Genus Poecilochirus (Acari: Mesostigmata: Parasitidae) Predacious on House Fly Eggs and Larvae

Abstract: Poecilochirus monospinosus Wise, Hennessey & Axtell, new species, is described from specimens collected and reared from poultry manure from Chatham and Wake Counties,. N.C. The larva, protonymph, deutonymph, and adult stages are described and figured. Data are given on the duration of the life stages, fecundity, and rates of predation by deutonymphs and adult females on house fly (Musca domestica L.) eggs and first instars at 26.6°C. Keys are given to the deutonymphs, females, and males of the described specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 5 publications
2
21
0
Order By: Relevance
“…Predation on different fl y larvae ( Fig. 1.4 ) is reported for several parasitids, including Parasitus bituberosus Karg (Karg 1972 ;Al-Amidi and Downes 1990 ), Parasitus coleoptratorum (L.) (Axtell 1986 ), Parasitus gregarius Ito (Ito 1977 ) and Poecilochirus monospinosus Wise, Henessey and Axtell (Axtell 1986 ;Axtell and Rutz 1986 ;Wise et al 1988 ).…”
Section: Biological Informationmentioning
confidence: 96%
See 2 more Smart Citations
“…Predation on different fl y larvae ( Fig. 1.4 ) is reported for several parasitids, including Parasitus bituberosus Karg (Karg 1972 ;Al-Amidi and Downes 1990 ), Parasitus coleoptratorum (L.) (Axtell 1986 ), Parasitus gregarius Ito (Ito 1977 ) and Poecilochirus monospinosus Wise, Henessey and Axtell (Axtell 1986 ;Axtell and Rutz 1986 ;Wise et al 1988 ).…”
Section: Biological Informationmentioning
confidence: 96%
“…Rapp ( 1959 ) cited the crucial importance of the presence of manure in the rearing chamber for the development of deutonymphs of P. coleoptratorum . Wise et al ( 1988 ) observed that survivorship and molting of deutonymphs of P. monospinosus to adults were greatly improved in the presence of fresh chicken manure.…”
Section: Practical Use In Biological Control Programsmentioning
confidence: 98%
See 1 more Smart Citation
“…The adult forms of these mites are free-living predators and feed mainly on fly eggs and first instar larvae. The female of M. glaber and P. carabi can destroy more than 13-18 fly eggs a day (14,19). There are only a few published data about the potential prey abundance (20).…”
Section: Resultsmentioning
confidence: 99%
“…Different species of the family Parasitidae have been reported to prey on house fly (Musca domestica L.) eggs, free-living nematodes (Rhabditella sp.) and on other mites (Wise et al, 1988;Lesna et al, 1995). The second most abundant species, G. aculeifer, is a well-known predator of various pests such as the worldwide invasive thrips F. occidentalis (Glockemann, 1992;Thoeming and Poehling, 2006).…”
Section: Discussionmentioning
confidence: 99%